Neuroprotective effects of erythromycin on ischemic injury following permanent focal cerebral ischemia in rats. (3rd March 2016) - Katayama, Yasuo; Inaba, Toshiki; Nito, Chikako; Ueda, Masayuki
Abstract : Objective: This study aims to determine if erythromycin provides neuroprotective effects against ischemic injury following permanent focal cerebral ischemia. Methods: Sprague–Dawley rats were subjected to middle cerebral artery occlusion (MCAO). Each animal received a single subcutaneous injection of erythromycin lactobionate (EM, 50 mg/kg) or vehicle immediately after ischemia. The infarct volume, edema index and neurological performance were evaluated at 24 and 72 h after MCAO. The cerebral blood flow (CBF) was measured with an MRI system at 30 min after MCAO. TUNEL staining and immunohistochemical analyses for oxidative stress (4-HNE, 8-OHdG) and inflammation (Iba-1, TNF-α) in the cortex were conducted at 24 and 72 h after MCAO. Results: The CBF did not differ between the EM-treated and vehicle-treated groups. The EM treatment significantly reduced the infarct volume ( p < 0.01) at 24 and 72 h after MCAO and significantly reduced the edema index ( p < 0.01) at 24 h. The EM treatment significantly improved the neurological deficit scores ( p < 0.05) at 24 and 72 h. EM also significantly suppressed the accumulation of 4-HNE ( p < 0.01) and 8-OHdG ( p < 0.01) and markedly reduced Iba-1 ( p < 0.01) and TNF-α expression ( p < 0.05) at both time points. The EM treatment significantly reduced TUNEL-positive cells ( p < 0.01) at both time points. Conclusion: These findings suggest that EM can protect against the neuronal damage caused by cerebral ischemia by alleviating inflammation and reducing oxidant stress.